Identification of a plasma miRNA biomarker signature for allergic asthma: A translational approach. Issue 12 (19th June 2017) - Milger, K.; Götschke, J.; Krause, L.; Nathan, P.; Alessandrini, F.; Tufman, A.; Fischer, R.; Bartel, S.; Theis, F. J.; Behr, J.; Dehmel, S.; Mueller, N. S.; et al.
Abstract: Background: Asthma is a heterogeneous chronic disease with different phenotypes and treatment responses. Thus, there is a high clinical need for molecular disease biomarkers to aid in differentiating these distinct phenotypes. As MicroRNAs (miRNAs), that regulate gene expression at the post‐transcriptional level, are altered in experimental and human asthma, circulating miRNAs are attractive candidates for the identification of novel biomarkers. This study aimed to identify plasmatic miRNA‐based biomarkers of asthma, through a translational approach. Methods: We prescreened miRNAs in plasma samples from two different murine models of experimental asthma (ovalbumin and house dust mite); miRNAs deregulated in both models were further tested in a human training cohort of 20 asthma patients and 9 healthy controls. Candidate miRNAs were then validated in a second, independent group of 26 asthma patients and 12 healthy controls. Results: Ten miRNA ratios consisting of 13 miRNAs were differentially regulated in both murine models. Measuring these miRNAs in the training cohort identified a biomarker signature consisting of five miRNA ratios (7 miRNAs). This signature showed a good sensitivity and specificity in the test cohort with an area under the receiver operating characteristic curve (AUC) of 0.92. Correlation of miRNA ratios with clinical characteristics further revealed associations with FVC % predicted, and oral corticosteroid or antileukotriene use. Conclusion: Distinct plasma miRNAs are differentially regulated both in murine and in human allergic asthma and were associated with clinical characteristics of patients. Thus, we suggest that miRNA levels in plasma might have future potential to subphenotype patients with asthma.